Cartilage exposure following autologous microtia reconstruction: An algorithmic treatment approach✰. Issue 3 (March 2019) - Cugno, Sabrina; Bulstrode, Neil W.
Summary: Background: Successful reconstruction of microtia involves fabrication of a cartilaginous framework and provision of thin, durable, soft tissue cover. Vascular compromise of this skin envelope can lead to exposure of the underlying cartilage, resulting in cartilage resorption and distortion of the final form of the ear construct. We describe our algorithm for management of this complication. Methods: All patients who underwent autologous ear reconstruction by a single surgeon (NWB) from April 2006 to September 2012 were retrospectively reviewed to identify any that developed exposure of the underlying cartilage framework. Details related to timing, location, size and management of the cartilage exposure were collected. Results: From a total of 230 autologous auricular reconstructions (median age at first stage, 11.4 years), 15 exposures of the cartilage framework were identified. All exposures occurred following the first stage of reconstruction (mean of post-operative day 29, range, 7–86 days). Large areas of exposure (> 10 mm2) required surgical management, with debridement and coverage with either a cutaneous or fascial flap, depending on the location. Areas < 10 mm2 were managed conservatively. All exposures were successfully treated with no adverse effects on the final aesthetic outcome. Conclusion: Cartilage exposure following autologous microtia reconstruction can be a devastating complication if not addressed in a prompt and effective manner. The management strategy we propose provides a concise algorithm to guide the treatment of cartilage exposure. Level of evidence: Therapeutic, grade III.